A heterogenized Ni-doped zeolitic imidazolate framework to guide efficient trapping and catalytic conversion of polysulfides for greatly improved lithium–sulfur batteries. Issue 28 (3rd July 2018) - Yang, Yuxiang; Wang, Zhenhua; Jiang, Taizhi; Dong, Chen; Mao, Zhu; Lu, Chengyi; Sun, Wang; Sun, Kening
Abstract : Ni-Doped ZIF-8 (Ni-ZIF-8) not only restrains the shuttling of LiPSs by chemical adsorption but also facilitates the redox reaction kinetics. Abstract : While lithium–sulfur (Li–S) batteries are poised to be the next generation of high-density energy storage devices, the intrinsic polysulfide shuttle has limited their practical applications. In order to fundamentally solve the problem, a well-designed host to simultaneously meet the requirements for both sufficient surface reaction and efficient conversion of polysulfides is urgently demanded. Herein, a 3D heterogeneous sulfur host, termed Ni-ZIF-8@CC, is fabricated by in situ deposition of nickel-doped zeolitic imidazolate framework-8 (Ni-ZIF-8) on carbon cloth (CC). Spectroscopic investigations show that polysulfides can be strongly adsorbed by the Ni-ZIF-8@CC host through the synergy between Ni–S and Li–N interactions, which is also verified by DFT simulations. The doped electrocatalytically active nickel species could furthermore significantly facilitate the kinetics of polysulfide redox reaction, attributed to fast lithium ion diffusion and reduced polarization potential. By combining these advantages, the electrodes exhibit a high areal capacity of up to 6.04 mA h cm −2 together with excellent cycling stabilities.